Moderating the effect of procurement governance on corruption through e-procurement - Suardi, Imelda; Rossieta, Hilda; Diyanty, Vera; Djakman, Chaerul (Integritas: Jurnal Antikorupsi, 2025)
E-procurement has become an obligation in the Indonesian government. However, its implementation has not been maximized. E-procurement can provide opportunities for corruption due to weak procurement governance. This study examines how governance based on government regulations and global recommendations can reduce corruption during the planning, preparation, and implementation phases of procurement. This study also examines the influence and role of e-procurement in strengthening the influence of procurement governance in reducing corruption from the perception of system users. This study collected primary data by distributing questionnaires to the ministries, institutions, provincial governments, and suppliers. The Smartpls Structural Equation Model (SEM) was used to test the hypotheses. The results prove that procurement governance has a significant impact on procurement corruption. These results imply that the principles of efficiency, capacity, competition, and monitoring and control are strongly correlated with procurement governance. In addition, corruption is most likely to occur in the procurement preparation stage. The test results also show that e-procurement is not directly significant in reducing corruption, but can strengthen the influence of governance on corruption.